2021
DOI: 10.48550/arxiv.2103.16876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring Coulomb-Induced Ionization Time Lag with a Calibrated Attoclock

et al.

Abstract: Electrons in atoms and molecules can not react immediately to the action of intense laser field. A time lag (about 100 attoseconds) between instants of the field maximum and the ionizationrate maximum emerges. This lag characterizes the response time of the electronic wave function to the strong-field ionization event and has important effects on subsequent ultrafast dynamics of the ionized electron. The absolute time lag is not accessible in experiments. Here, a calibrated attoclock procedure, which is relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Further studies also show that due to the PD effect, there is a difference of the response time of polar molecules between the first half of the laser cycle and the second half. The difference can be characterized by the ratio of the PMD in different quadrants in the orthogonal two-color field [39], and also by the offset angle of the PMD in the elliptically-polarized laser field [40]. Considering the Coulomb-induced temporal correction to electron trajectory, the usual attoclock can be calibrated to establish a direct one-to-one correspondence between time and photoelectron momentum.…”
Section: Strong-field Response Time and Its Effects On Attosecond Mea...mentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies also show that due to the PD effect, there is a difference of the response time of polar molecules between the first half of the laser cycle and the second half. The difference can be characterized by the ratio of the PMD in different quadrants in the orthogonal two-color field [39], and also by the offset angle of the PMD in the elliptically-polarized laser field [40]. Considering the Coulomb-induced temporal correction to electron trajectory, the usual attoclock can be calibrated to establish a direct one-to-one correspondence between time and photoelectron momentum.…”
Section: Strong-field Response Time and Its Effects On Attosecond Mea...mentioning
confidence: 99%
“…Considering the Coulomb-induced temporal correction to electron trajectory, the usual attoclock can be calibrated to establish a direct one-to-one correspondence between time and photoelectron momentum. Then the response time can be read directly from the Coulomb-corrected attoclock, especially the relative response time between different electronic states [40].…”
Section: Strong-field Response Time and Its Effects On Attosecond Mea...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown that the Coulomb effect can induce a large ionization time lag [21] relative to SM and SFA predictions. The inclusion of the time lag into the SM mapping relation is able to qualitatively explain complex strong-field phenomena [21][22][23]. However, a general theory description for this lag is not acquirable and the physical origin of this lag is unclear.…”
mentioning
confidence: 99%
“…Here, γ L = w 2I p /E L is the Keldysh parameter [27]. A similar expression to the adiabatic one has been used in [23] to deduce the lag τ and has been termed as Coulombcalibrated attoclock (CCAC). Here, the theory description is given.…”
mentioning
confidence: 99%